Análisis teórico y jurídico de las funciones de los gobiernos autónomos descentralizados provinciales.- propuesta de reforma al art. 41 del COOTAD - Reinoso Mora, María Dalinda (2018)
The matrix problem generated after the process of analysis and deduction prior recognition of the techniques and procedures of a legal investigation of applied character, focuses on the review and theoretical study of important institutions and legal figures of relevant connotation in the area of positive law. The analysis of the problem object of study focuses on the system of territorial organization in Ecuador and their levels of government, which implies the revision of the land code to identify the constraints of a structural nature that are observed in the operation of the decentralized autonomous governments and mainly from those which govern the scope and provincial administration; the autonomous governments decentralized provincial are legal persons of public law, with autonomy political, administrative and financial. Will be integrated by the functions of citizen participation; legislation and control; and, executive, provided for in this Code, for the exercise of the functions and responsibilities assigned to it. The headquarters of the government decentralized autonomous provincial will be the capital of the province provided for in the respective founding law. The existing problem i think is based in the inability of the decentralized autonomous governments to issue normative acts that allows them to generate the collection of taxs within the appropriate territorial level, with the object of self-finance the execution of public works and services for the province; it is therefore necessary to incorporate an attribution to the decentralized autonomous governments can create ordinances in the field of creation and tax collection, considering the troubled economic situation of the provincial councils that have been forced to stop the management of major projects and construction of public works and services by the insufficiency of resources and income generated by the indiscriminate delay of budgetary allocations by the central government.